Human platelet lysate standardization across three independent European blood establishments - Willem Delabie; Gabriele Boretti; Stephanie A. Groot; Davina Ardanary; Olafur Sigurjónsson; Thomas R. L. Klei; Philippe Vandekerckhove; Hendrik B. Feys (Stem Cell Research & Therapy)
Abstract Human platelet lysate (hPL) is a clinically safe alternative to fetal bovine serum (FBS). However, variability in blood donation practices, platelet concentrate preparation methods, storage and hPL manufacturing complicates standardization across jurisdictions. This study aimed to establish a first multinational hPL manufacturing standardization across three European blood centers to test feasibility and variability. A single batch of hPL production sets was distributed to the participating centers. There, hPL was produced following a single standard operating protocol but starting from each center’s unique platelet concentrates. Each center prepared four ‘national’ hPL batches and four ‘international’ batches. Researchers conducted blinded quality and variation analyses to ensure unbiased results. All hPL batches exhibited comparable total protein levels, pH, ionic strength, and lactate content. Analysis of twelve growth factors showed minor variations across batches. Endothelial cell outgrowth and wound closure were slower in hPL than FBS but remained consistent across batches. Mesenchymal stem cell (MSC) doubling was significantly faster in hPL than in FBS, with MSC phenotype consistency confirmed via flow cytometry. Differentiation into adipogenic and osteogenic tissue was successful in all hPL samples. The inter-institutional variation across all national batches was higher for all critical outcome parameters compared to the variation in the four international batches. These findings confirm the feasibility of manufacturing standardized hPL across borders and show lower variability when doing so. This supports further efforts to stabilize hPL supply and advance cytotherapy standardization in Europe.